Literature Teaching Forms Student Character - Simarmata, Radode Kristianto (Future Science / FSH-PH Publications, 2023)
The teaching of literature involves strengthening awareness about ethical attitudes . Literature is considered less important and has less role in society. HKBP University English Education Students Nommensen Pematangsiantar are the young generation, the next generation, who will become the owners of a diverse and unique nation's future . This research aspect (research focus) is to form a commendable moral culture/character in the acquisition of literary teaching which is evident in the influence of the sensitivity factor of a person's feelings who have studied a lot in various literary works in showing which things are valuable and which are not valuable (ethical culture/character noble character/ The Character Building ) with the 3P method (touching, awakening, and developing conscience). object Research (type of material to be studied and research aspects) attitude and character of English Language Education Study Program students at HKBP Nommensen Pematangsiantar University in teaching literature. The research subjects were 15 English Language Education Students at HKBP Nommensen Pematangsiantar University. Teaching literature using the 3P method which pivots on motivation has succeeded in changing the mind-set of the way of thinking of English Language Education Students at HKBP Nommensen Pematangsiantar University so that the character of noble character is formed.